Pig kidney graft survival in a baboon for 136 days: longest life‐supporting organ graft survival to date. (29th June 2015) - Iwase, Hayato; Liu, Hong; Wijkstrom, Martin; Zhou, Huidong; Singh, Jagjit; Hara, Hidetaka; Ezzelarab, Mohamed; Long, Cassandra; Klein, Edwin; Wagner, Robert; Phelps, Carol; Ayares, David; et al.
Abstract The longest survival of a non‐human primate with a life‐supporting kidney graft to date has been 90 days, although graft survival > 30 days has been unusual. A baboon received a kidney graft from an α‐1, 3‐galactosyltransferase gene‐knockout pig transgenic for two human complement‐regulatory proteins and three human coagulation‐regulatory proteins (although only one was expressed in the kidney). Immunosuppressive therapy was with ATG+anti‐CD20mAb (induction) and anti‐CD40mAb+rapamycin+corticosteroids (maintenance). Anti‐TNF‐α and anti‐IL‐6R were administered. The baboon survived 136 days with a generally stable serum creatinine (0.6 to 1.6 mg/dl) until termination. No features of a consumptive coagulopathy (e.g., thrombocytopenia, decreased fibrinogen) or of a protein‐losing nephropathy were observed. There was no evidence of an elicited anti‐pig antibody response. Death was from septic shock (Myroides spp). Histology of a biopsy on day 103 was normal, but by day 136, the kidney showed features of glomerular enlargement, thrombi, and mesangial expansion. The combination of (i) a graft from a specific genetically engineered pig, (ii) an effective immunosuppressive regimen, and (iii) anti‐inflammatory agents prevented immune injury and a protein‐losing nephropathy, and delayed coagulation dysfunction. This outcome encourages us that clinical renal xenotransplantation may become a reality.